2003
DOI: 10.1034/j.1600-0404.2003.02155.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressed mood and executive dysfunction in early Parkinson's disease

Abstract: In summary the present results indicate that depressed mood in early PD may exacerbate cognitive impairments. Thus careful assessment of affective variables in PD should be an integral part of the treatment of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 31 publications
2
43
3
1
Order By: Relevance
“…These studies should not only elucidate mechanisms of cognitive dysfunction in PD, but more generally provide a readily available tool to study important neuropsychiatric functions of the basal ganglia and DA. As an example of this depression, which occurs in greater than 40% of patients with PD and executive dysfunction are common and disabling features of PD which are not well understood (Uekermann, Daum et al 2003;Lemke, Fuchs et al 2004;Weintraub, Moberg et al 2005). Without gross motor impairment as a potential confound ak mice are well suited to be used as a DA-deficiency model to study these and other important neuropsychiatric features of PD.…”
Section: Discussionmentioning
confidence: 99%
“…These studies should not only elucidate mechanisms of cognitive dysfunction in PD, but more generally provide a readily available tool to study important neuropsychiatric functions of the basal ganglia and DA. As an example of this depression, which occurs in greater than 40% of patients with PD and executive dysfunction are common and disabling features of PD which are not well understood (Uekermann, Daum et al 2003;Lemke, Fuchs et al 2004;Weintraub, Moberg et al 2005). Without gross motor impairment as a potential confound ak mice are well suited to be used as a DA-deficiency model to study these and other important neuropsychiatric features of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between depression and cognitive impairments in PD patients [22][23][24][25][26][27][28][29][30]. There are, however, a few other studies that did not detect a significant association between depression and variance in cognitive deficit in PD (See table 1) [31][32][33][34].…”
Section: Depressionmentioning
confidence: 99%
“…In terms of executive dysfunction, several studies have reported that patients with depression performed significantly lower than non-depressed patients on tests of executive function including the Wisconsin Card Sort Test (WCST) [35], Controlled Word Association Test-FAS [36], Trail Making Test (TMT) (A and B) [37], Verbal Fluency, Abstract Reasoning, Design Fluency Test (Free condition) [38] and the Symbol Digit Modalities [39], [25,28,30] . Other studies have also demonstrated that depressed PD patients had lower scores relative to non-depressed PD patients using a variety of executive tasks e.g.…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, depressed patients with PD have signifi cantly greater impairments in attention and working memory (Uekermann et al 2003) and perform more poorly on neuropsychological measures of frontal/executive function (ie, Wisconsin Card Sorting Test and Raven Progressive Matrices) than non-depressed patients with PD (Kuzis et al 1997). Other studies have bolstered these fi ndings in showing that depression at baseline increases the risk for developing dementia later in PD Stern et al 1993;Hughes et al 2000).…”
Section: Depression and Associated Health Risks In Pd Depression And mentioning
confidence: 52%